Analisis Hambatan dan Solusi dalam Penerapan Kurikulum Merdeka di SDN Jomblang 03 - Startyaningsih, Theresia; Sumarno, Sumarno; Dwijayanti, Ida (Medan Resource Center, 2024)
This article analyzes the obstacles faced in implementing the Merdeka Curriculum at SDN Jomblang 03, Candisari Sub-district, and provides solutions to overcome these challenges. Using a descriptive method, data were collected through observation, interviews, and document analysis. The data were analyzed to identify obstacles and formulate solutions. The study found that SDN Jomblang 03 has implemented the Merdeka Curriculum in grades 1, 2, 4, and 5, shifting the focus from teacher-centered to student-centered learning. Despite progress, obstacles such as limited resources, difficulties in formative assessment, the need for curriculum development, challenges in parental and community involvement, and resistance to changes in learning culture persist. The findings suggest positive potential for the Merdeka Curriculum but highlight significant barriers. Proposed solutions include optimizing resources, training teachers in formative assessment, providing clear curriculum development guidelines, fostering active parental and community involvement, and effectively communicating the benefits of the Merdeka Curriculum.